2013
DOI: 10.1161/circep.113.000111
|View full text |Cite|
|
Sign up to set email alerts
|

Sudden Cardiac Death With Autopsy Findings of Uncertain Significance

Abstract: Background-The sudden death of young individuals is commonly attributed to inherited cardiac disorders, and familial evaluation is advocated. The identification of pathognomonic histopathologic findings, or the absence of cardiac pathology (sudden arrhythmic death syndrome [SADS]) at postmortem, directs familial evaluation targeting structural disorders or primary arrhythmogenic syndromes, respectively. In a proportion of autopsies, structural abnormalities of uncertain significance are reported. We explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 34 publications
3
105
1
2
Order By: Relevance
“…[24][25][26][27] Children 6 to 10 years of age had the lowest rate of sudden cardiac death (0.8%), after which the risk increased, as reported previously. 28,29 The incidence of cardiomyopathy (hypertrophic cardiomyopathy, dilated cardiomyopathy, and arrhythmogenic right ventricular cardiomyopathy) as a cause of sudden cardiac death among children and young adults in our study was lower than that observed in previous studies 30 ; this finding may reflect improved diagnosis and management in recent years, including the appropriate use of implantable cardioverter-defibrillator therapy. [31][32][33] Coronary artery disease was the …”
Section: Discussioncontrasting
confidence: 68%
“…[24][25][26][27] Children 6 to 10 years of age had the lowest rate of sudden cardiac death (0.8%), after which the risk increased, as reported previously. 28,29 The incidence of cardiomyopathy (hypertrophic cardiomyopathy, dilated cardiomyopathy, and arrhythmogenic right ventricular cardiomyopathy) as a cause of sudden cardiac death among children and young adults in our study was lower than that observed in previous studies 30 ; this finding may reflect improved diagnosis and management in recent years, including the appropriate use of implantable cardioverter-defibrillator therapy. [31][32][33] Coronary artery disease was the …”
Section: Discussioncontrasting
confidence: 68%
“…Others have reported sequence results for disease-specific genetic panels with smaller cohorts or full exome analysis of specific individuals (Ackerman et al 2004;Tester et al 2005Tester et al , 2012Papadakis et al 2013;Brion et al 2014). In this study, we incorporated many genes previously included in separate disease-specific assays into one comprehensive genetic screening panel.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results from this study and others are consistent in finding an inactive or asleep mode of death among most SADS cases, it is important not to limit investigations in adults to more likely conditions because there will always be a range of circumstances of death regardless of the ultimate familial diagnosis. 7,13,17 Ajmaline testing may be considered in children without a diagnosis from undiagnosed families and after careful discussion with parents but if delayed may best be undertaken before discharge from the pediatric ICC clinic and before transition to adult services. In the interim, advice may be given about lifestyle such as careful monitoring when exposed to drugs that exacerbate BrS and prompt treatment of fever.…”
Section: A Proposal For Pediatric Management Pathways In Sads Familiesmentioning
confidence: 99%